PREDICTING CORPORATE BANKRUPTCY IN INDONESIA'S TRANSPORTATION INDUSTRY - Surwanti, Arni; Fauzi, Ramdan; Masruki, Rosnia (Universitas Brawijaya, Indonesia, 2022)
This study predicts the potential bankruptcy of transportation firms listed on the Indonesia Stock Exchange in 2014-2019. Three prediction models are modified Altman Z-score, Springate Score, and Zmijewski Score. This study also aims to determine the determinants of bankruptcy according to the three models. Archival techniques are used to collect data. Based on the modified Altman Z-score, 65 companies are in the potentially bankrupt category, while 39 companies are healthy. According to the model, the determinants of bankruptcy are profitability and market value. Based on the Springate model, there are 115 firms in the potentially bankrupt category and 17 companies in the healthy category. The determinants of bankruptcy are working capital, profitability, and activity. Zmijewski's model suggests that 111 firms are healthy and 21 are in the bankrupt category. It shows that profitability and solvency are significant predictors of bankruptcy. This paper is a compilation of the concerns surrounding corporate bankruptcy risk, issues that each company manager should be aware of to secure business continuity. Investors also need to consider this company's bankruptcy prediction analysis to determine investment choices. The government also needs to evaluate the policy for the transportation industry.